Healthcare Support Related to Family Awareness Efforts Towards The Risk of Stunting in Children - Ni Luh Kompyang Sulisnadewi; I Ketut Gama; Ida Erni Sipahutar; I Wayan Suardana; Yupin Aungsuroch (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Preventing stunting necessitates collaborative efforts from multiple stakeholders, with the family being the most pertinent social unit in guaranteeing adequate nutrition for children. The study aimed to examine the correlation between healthcare supports and family efforts in raising awareness about the risk of stunting in young children. This study used a cross-sectional survey that examined family characteristics and various efforts to prevent stunting in children within the community. In addition, the study investigated healthcare support and family awareness. A total of 200 mothers from families with stunted children participated in the study. Data were collected using questionnaires and analyzed descriptively. Rank Spearman Correlation was used to investigate the correlation between healthcare worker support and the behaviors of mothers of toddlers with stunting before marriage, during pregnancy, and while breastfeeding. The average age of mothers was 29.6 years, with the youngest being 20 and the oldest 46 years. The majority of the mothers had a high school education, were housewives, came from nuclear families, had access to clean drinking water, lived in clean and well-maintained homes, and had incomes below the regional minimum wage. Efforts to prevent stunting were fair before pregnancy, during pregnancy, and while breastfeeding. Most of the support from healthcare workers in preventing stunting were classified as good. The analysis results indicate a significant positive relationship between healthcare worker support and the behaviours of mothers of toddlers with stunting, both before marriage and while breastfeeding (p<0.05). Our findings revealed that stunting was observed in families of productive age, with high school education, nuclear family structures, and low economic income below the regional minimum wage. Preventive efforts have been made since before marriage, during pregnancy, and while breastfeeding, but have not been fully optimized. Support from healthcare workers must be continually improved to meet the healthcare needs of families in an effort to prevent stunting in children.